Óleos essenciais e seus compostos puros no controle de células planctônica e sésseis de cepas de Bacillus cereus - Domingues, Aparecida Sílvia (2015)
Microbial biofilms are a major problem for the food industry and their disposal has been the subject of several studies. So the first step of this research was conducted in order to evaluate the bactericidal activity of essential oils of cardamom, lemon grass, thyme, cloves and cinnamon and of pure compounds citral (CIT), thymol (TIM), α-terpineol (TER), cinnamaldehyde (CIN) and eugenol (EUG) against planktonic cells and sessile of Bacillus cereus strains ATCC 14579, ATCC11778, CCT 2897 and CCT 7453. The concentration minimum inhibitory (CMIs) and concentration minimum bactericidal (CMBs) were determined by broth microdilution. All constituents showed antibacterial activity. The CIT and CIM solutions were the constituents that showed the best results in the previous test. These were tested against biofilms formed on stainless steel AISI # 304. CIT and CIN showed antibacterial effect also against sessile cells and may be new alternatives for the preparation of sanitizing. The second stage of this research was conducted in order to assess the exposure effect of the biofilm of B. cereus during their training, sublethal concentrations CIN and CIT. By the number of sessile cells after 48 hours of training, it was found that exposure to sublethal concentrations of C IN and CIT affect biofilm formation in Bacillus cereus strains can make it more resistant to these compounds as well as more sensitive, the Cross-way or not, the occurrence of these effects are dependent on the strain, and the compound being employed.